A-priori estimates of the hp-adaptive BEM in elastic scattering of acoustic waves - Karafiat, Andrzej (Computer Assisted Methods in Engineering and Science, 2023)
In the paper some a-priori hp-adaptive error estimates, applied to the problem of acoustic wave scattering on an elastic body in the 2D space, solved by the Boundary Element Method, are presented. The estimate includes both the function- and boundary approximation errors.